DAYA SAING DAN ANJAKAN (SHIFT) DALAM JENIS KONTRAK PEMBIAYAAN PERBANKAN ISLAM - Mohd Hussin, Mohd Yahya; Muhammad, Fidlizan; Awang, Salwa Amirah; Kamri, Nor 'Azzah (Jurnal Syariah, 2010)
This study aims to research the changing trend in the use of contract types in Islamic banking financing in Malaysia for the year of 2007 and 2008. In this research, monthly data for each type of financing concept is applied. The data is analyzed via the shift-share technique. Based on the findings, it is found that Islamic banking financing tends to apply the contract of Murabahah and Ijarah. Meanwhile, results shown that there is a decrease in the use of the contract riding on Bay‘ bi Thaman Ajil.